How Household Tourism Expenditure in Indonesia? A QUAIDS Model Analysis - Imron Rosyadi; Salsabila Avrillia (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Tourism is a sector in Indonesia that has experienced rapid development in the last decade. This sector provides new hope for the emergence of new sources of economic growth when the economy is experiencing a slowdown. This study aims to estimate the income elasticity and expenditure pattern household on tourism in Indonesia. The data used is the publication of the Indonesian Family Life Survey (IFLS). To obtain comprehensive estimation results, this study uses the Quadratic Almost Ideal Demand System (QUAIDS) approach which is currently the standard in household demand estimation systems. Four groups of expenditure types were examined: personal goods, household goods, tourism, and transportation. The results showed that the largest household expenditure was transportation followed by personal goods, household goods, and tourism. However, the largest household income elasticity is tourism, followed by household goods, personal goods and transportation. This is because when household income is constant, the household expenditure budget is allocated to transportation, personal goods and household goods more than tourism. Meanwhile, when income increases, households will allocate their budget for tourism, because expenditure on transportation, personal goods, and household goods has reached the point of maximum utility. And then, other finding show that income elasticity is relatively elastic. This suggests that improvements in household income have the potential to increase expenditure on the tourism sector. This has important implications in terms of public policy, as it makes it possible to explore how tourism policy interacts with household expenditure. Thus, the government and related institutions can obtain consideration from income elasticity and expenditure pattern household in making policies in the tourism sector.